2020
DOI: 10.3389/fpsyt.2020.00530
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Bipolar Disorder and Low Bone Mass: A Cross-Sectional Study With Newly Diagnosed, Drug-Naïve Patients

Abstract: Background: Medical comorbidities in people with mental disorders have recently gained more attention. People with bipolar disorder (BD) often have comorbid low bone mass, which is associated with increased fracture risk and related severe outcomes. However, few clinical studies on bone metabolism in BD patients are available. This study was designed to assess bone mineral density (BMD) and related influencing factors in a sample of newly diagnosed, drug-naïve individuals with BD and age-and sex-matched health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…1,2 Recent evidence suggests that bipolar disorder may be such a risk factor. [3][4][5] Bipolar disorder is a severe mental illness characterized by recurrent manic, hypomanic, depressive, and mixed episodes, which affects 1% to 2% of the population worldwide. 6,7 While manic and hypomanic episodes are defining for the disorder, it is the depressive episodes that account for the main burden of illness, [8][9][10] and depression is considered to be an important risk factor for poor bone health and osteoporosis, possibly mediated by lifestyle factors, such as poor diet and lack of physical activity or exercise.…”
mentioning
confidence: 99%
“…1,2 Recent evidence suggests that bipolar disorder may be such a risk factor. [3][4][5] Bipolar disorder is a severe mental illness characterized by recurrent manic, hypomanic, depressive, and mixed episodes, which affects 1% to 2% of the population worldwide. 6,7 While manic and hypomanic episodes are defining for the disorder, it is the depressive episodes that account for the main burden of illness, [8][9][10] and depression is considered to be an important risk factor for poor bone health and osteoporosis, possibly mediated by lifestyle factors, such as poor diet and lack of physical activity or exercise.…”
mentioning
confidence: 99%
“…Little is known about bone health in adults with bipolar disorder 43 and, to our knowledge, no research has examined heel bone mineral density in bipolar disorder. Research in Chinese adults found lower bone mineral density at other sites in drug-naïve bipolar disorder patients compared to healthy controls 44 . A 2019 review of three cohorts, one from the US and two from Taiwan, found higher fracture risk in individuals with bipolar disorder 45 but included no studies that directly examined bone mineral density.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that some factors, such as low physical activity or medication with antiepileptics or SGA, could have turned significant in a larger study sample. However, previous studies on antipsychotics or antiepileptics and fracture risk have not found any significant associations [ 5 , 23 ], and low BMD have been shown to be more common in bipolar disorder already at the time of diagnosis [ 12 ]. It is possible that some of the reasons for low BMD and the increased risk of fractures in bipolar disorder should be searched for earlier in bipolar patients’ lives.…”
Section: Discussionmentioning
confidence: 99%
“…Unipolar depression and schizophrenia have both been associated with osteoporosis and reduced BMD [ 9 , 10 ]. The association between BD and osteoporosis have been less clear [ 11 ], but recent studies conclude that patients with BD compared to the general population have a higher risk of fractures and osteoporosis [ 4 , 5 , 6 , 7 , 12 ]. However, the risk of low BMD seems to be lower in bipolar depression than in unipolar depression and schizophrenia [ 13 ].…”
Section: Introductionmentioning
confidence: 99%